Penerapan Enterprise Resource Planning Berbasis Odoo pada Modul CRM (Studi Kasus UMKM Credeva) - Rahmatila, Aira; W, Ruben Emmanuel; R, Dwi Randi; P, Yusril Adriansyah (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 3 (2022): JITTER, Vol.3, No.3, December 2022DO - 10.24843/JTRTI.2022.v03.i03.p05, 2022)
UMKM Credeva is one of the UMKM website design and programming services located in the Duduk Sampeyan area, Gresik City. Enterprise Resource Planning (ERP) software is a system that integrates all business processes, from inventory, accounting and finance, resource management, and so on. By using ERP software, companies get several benefits, including: increased efficiency & productivity, planning & information management, process standardization, and of course better business integration & data accuracy. The accuracy of this data is very important to see the amount of data that is in the business processes of a company, especially medium and large companies. The Odoo UMKM Credeva implementation project was carried out because it saw problems in its business processes. The problem is in Relationship Management between customers because it is still not optimal when there are many overloads on incoming orders because they are still using manual recording. Then the problem that often occurs is the negligence of not recording the order deadline to the customer. As well as other problems, lack of understanding of the use of customer management where employees are still minimal. This results in a gap between reports and delays in accessing information to customer requests. So that Odoo is very much needed in carrying out business processes going forward. In this plan, will provide a module on CRM (customer relationship management)